1990
DOI: 10.1093/jn/120.12.1633
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution and Prediction of Total Body Folate of Rats

Abstract: To clarify relationships between dietary folic acid intake, blood levels and body stores of folate, rats were fed an amino acid-based diet supplemented with 0, 0.125, 0.5, 1, 2 or 4 mg folic acid/kg diet for 25 d. Folate concentrations of carcass, liver, gastrointestinal (GI) tract, kidney, spleen, testes, heart and lung from rats fed the folate-free diet were 0.06 +/- 0.01, 0.73 +/- 0.08, 0.05 +/- 0.01, 0.39 +/- 0.01, 0.05 +/- 0.01, 0.17 +/- 0.01, 0.02 +/- 0.01 and 0.02 +/- 0.01 micrograms/g, respectively. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
0
3

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 14 publications
6
20
0
3
Order By: Relevance
“…Since the folate level decreases in plasma before its tissue depletion, and this decrease in plasma is paralleled by a reduction in red blood cell folate, the levels in plasma are important clinical indicators that reflect the folate status of the body of many mammalian species (1, 2,5,8). It has been reported that serum folate levels decrease during pregnancy in pigs (11).…”
Section: Introductionmentioning
confidence: 99%
“…Since the folate level decreases in plasma before its tissue depletion, and this decrease in plasma is paralleled by a reduction in red blood cell folate, the levels in plasma are important clinical indicators that reflect the folate status of the body of many mammalian species (1, 2,5,8). It has been reported that serum folate levels decrease during pregnancy in pigs (11).…”
Section: Introductionmentioning
confidence: 99%
“…Folate intake directly influences the plasma folate concentrations, whereas tissue folate levels saturate at high folate intakes (Clifford et al 1990). To elevate the tissue folate levels, dose of 5-formyl-THF are more beneficial than folic acid or 5-methyl-THF.…”
Section: Discussionmentioning
confidence: 99%
“…26 Nonetheless, mammalian cells are not able to uptake long chain length of polyglutamates (three and above). 27 The liver is able to absorb much of the folate that entered the portal circulation.…”
Section: Tissue Uptakementioning
confidence: 99%